The Influence of Monitor Comprehension towards Students’ Reading Comprehension Achievement - Elya Anggraini; Warno Edi; Yuli Angraini (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
This research was about Monitor Comprehension Strategy (MCS) to the reading comprehension of students in class 8 SMPN 9 Batam in academic year 2015/2016. The purpose of this study was to find the influence of strategy on reading comprehension of students. To get the purpose of the study, researchers conducted research experiments. 5QAAnumber of students is 210. Researchers used a purposive sampling technique to determine the grade of research. The subject was VIII.4 and VIII.7 classes totaling 30 students each class. Researchers conduct research in two classes. The first class (VIII.4) as experimental class and the second class (VIII.7) as the control class. In analyzing the data researchers used quantitative calculation to find the result. Data were analyzed showed significant differences before getting treatment for an average of 67.50 and 67.17 for the control class. The average score obtained student after getting treatment in the experimental class are 82.50 and 78.50. Based on these result, the use of Monitor comprehension strategy gives significant influence on student’s reading comprehension. Keywords: students’ reading comprehension, monitor comprehension strategy